Spermiogenesis, Stages of Seminiferous Epithelium and Variations in Seminiferous Tubules during Active States of Spermatogenesis in Yangzhou Goose Ganders - Muhammad Faheem Akhtar; Ejaz Ahmad; Sheeraz Mustafa; Zhe Chen; Zhendan Shi; Fangxiong Shi (Animals, 2020)
The past three decades revolutionized the goose industry in the world. China holds the world’s largest goose breeds stock by 95% of the global total. To optimize the goose industry and cope with ever increasing poultry meat and egg demands, there is a dire need to focus on reproduction, as most geese breeds exhibit poor reproductive performance. The present study was conducted with the aim to add a contribution in the goose industry and research by the histological visualizing step wise development of germ cells during spermatogenesis by microscopy and a histological technique. Yangzhou goose is a synthetic breed developed by using local goose germplasm resources of China. It is popular in the Chinese goose industry due to high productivity and adaptability. This research evaluated the steps of spermiogenesis and stages along with morphological changes in the seminiferous epithelium in Yangzhou goose ganders. For the assessment of various stages of the seminiferous epithelium cycle, testis sections were embedded in molten paraffin wax. The initial steps of spermiogenesis were depicted by changes in acrosomic granules, whereas further stages were identified by nuclear morphological changes. Ten steps of spermiogenesis and nine stages of seminiferous epithelium were identified. Four types of spermatogonia Ad, Ap1, Ap2 and B were recognized. The results depicted a clear variation in the diameter of seminiferous tubules (ST), epithelium height (EH), luminal tubular diameter (LD), number of seminiferous tubules per field and the Johnsen score. Microscopy indicated that the stages of seminiferous epithelium were similar to other birds and mammals and the ST diameter, EH, LD and Johnsen score are positively correlated while the number of seminiferous tubules per field is negatively correlated with the ST diameter, EH, LD and Johnsen score. Fertility in Yangzhou ganders can further be improved by visualizing the histological development of germs cells in testis tissues during spermatogenesis after onset of breeding season and maturity. Our results suggest that Yangzhou ganders reach complete sexual maturity at 227 days of age.